أساليب المعاملة الوالدية وأثرها على مفهوم الذات والأمن النفسي لدى طلبة التعليم ما بعد الأساسي في ولاية المضيبي بسلطنة عمان - صوافي، محمد ناصر سعيد (Kulliyah of Education, International Islamic University Malaysia, 2020)
This study aims to identify the predictors students' level of self-concept and psychological security. The basic aim is to identify the effect of Parental Treatment Styles and its correlation to both the students' self – concept and psychological security in the post- basic education in Al Mudhaibi district, Oman. To achieve the research objectives, the descriptive method was used as well as pertinent instruments namely, the Parental Treatment scales, the Self-Concept scale, and Psychometric Security scale. Random sampling procedure was employed and 340 male and female students were identified in Al Mudhaibi schools from the academic year 2018/2019. Descriptive (means and standard deviations) and inferential statistic procedures (ttests, ANOVA and Multiple Regression Analysis) were used to analyze the real data. The findings showed that the prevailing styles among parents of the study sample is the method of equality between the sons. The students' level of self-concept was high and their level of psychological security was just average. The results also showed that there were no significant differences in the Parental Treatment Styles, as perceived by children. This could be attributed by the educational level of the father in all Parental Treatment Styles except for the control method. As for mothers' educational level, no significant parental treatment was found except for the overlyprotected parental treatment. Significant differences were found in the Parental Treatment Styles based on the number of siblings in the family and not indicated by the children's birth order. No significant gender differences were found in the Parental Treatment Styles except for the overly-protected dimension. There were no significant gender differences found in the students' level of self-concept and their level of psychological security. Findings from the MRA analysis too indicated the students' level of Psychological Security, and Self-Concept were significantly predicted by their parental treatment styles.